2018
DOI: 10.3329/bjz.v46i1.37629
|View full text |Cite
|
Sign up to set email alerts
|

Oxytetracycline residues in Thai pangas Pangasianodon hypophthalmus sampled from Sylhet sadar upazila, Bangladesh

Abstract: not availableBangladesh J. Zool. 46(1): 81-86, 2018

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In Bangladesh, 3,079 metric tons of poultry manure is produced per day and 50% of this is directly used in aquaculture [51]. For example detectable amount of oxytetracycline residues was traced in 25% Pangas fish samples from Sylhet Sadar [52]. This has resulted in the presence of pathogenic bacteria resistant to commonly used antimicrobials in water resources and salad vegetables which are significant from a public health perspective [53][54][55][56][57].…”
Section: Situation In Food Animals Fisheries and Environment Includmentioning
confidence: 99%
“…In Bangladesh, 3,079 metric tons of poultry manure is produced per day and 50% of this is directly used in aquaculture [51]. For example detectable amount of oxytetracycline residues was traced in 25% Pangas fish samples from Sylhet Sadar [52]. This has resulted in the presence of pathogenic bacteria resistant to commonly used antimicrobials in water resources and salad vegetables which are significant from a public health perspective [53][54][55][56][57].…”
Section: Situation In Food Animals Fisheries and Environment Includmentioning
confidence: 99%
“… Antibiotic concentrations are based on the following references ( Bakar et al, 2013 ; Barman et al, 2018 ; Chowdhury et al, 2015 ; Ferdous et al, 2019 ; Hossain et al, 2018 ; Sattar et al, 2014 ). …”
Section: Resultsmentioning
confidence: 99%
“…Humans consuming livestock and aquaculture-derived food products might have the chance to develop resistance against specific antimicrobials due to antimicrobial residues being introduced into the human food chain ( Roess et al, 2013 ). To investigate the situation of antimicrobial residues in animal-derived food, we consulted previous reports ( Bakar et al, 2013 ; Barman et al, 2018 ; Bristy et al, 2019 ; Chowdhury et al, 2015 ; Ferdous et al, 2019 ; Hossain et al, 2018 ; Islam et al, 2016 ; Khan et al, 2018 ; Sarker et al, 2018 ; Sattar et al, 2014 ). Some studies proposed different techniques for antimicrobial residue detection in different types of animal-derived food products.…”
Section: Introductionmentioning
confidence: 99%
“…The evolving resistance pathogen enter to humans with animals and biological substances (such as blood, urine, feces, milk, saliva, semen) and enhances the rapid transmission and risk of dissemination of resistant bacteria from host to host [4]. Some studies also demonstrated the presence of the residue of different antibiotics (ciprofloxacin, enrofloxacin, amoxicillin, doxycyline, oxytetracylcine, and tetracycline) in poultry meat [60], milk, eggs [61] and fishes [62] as well.…”
Section: Resistance Pathogen Originated From Human Foodmentioning
confidence: 99%